Eight legs, two wings, one life for scientific research—celebrating the 80th birthday of Prof. Dr Jochen Martens - Jäger, Peter; Schönhofer, Axel (Zootaxa, 2021)
The scientific life of Prof. Dr Jochen Martens (Germany: Mainz) is illuminated on occasion of his 80th birthday. Facts and impressions are given as well as lists of his publications (329), taxa he has described (2 families, 29 genera, 296 species) and that have been dedicated to him (11 genera, 219 species, 1 subspecies). Jochen Martens is a renowned specialist for birds (Aves) and for harvestmen (Opiliones). So far, he travelled to 27 countries in 80 journeys with Nepal and the Himalayas as one geographic focus.